Renal Autotransplant Results in Pain Resolution Following Left Renal Vein Transposition - Bath, Natalie (J Vasc Surg Venous Lymphat Disord, 2019)
Left renal vein (LRV) transposition is often the preferred treatment for Nutcracker syndrome (NCS). However, pain returns in some patients despite undergoing surgery. One solution to this problem is renal autotransplant. Here we report our initial results of renal autotransplant in patients with persistent flank pain despite a previous LRV transposition. We used the UW-LPHS (Loin Pain Hematuria Syndrome)-test as a diagnostic maneuver to determine who may benefit from renal autotransplant which this procedure subsequently resulted in complete pain resolution in all three patients. All patients underwent successful renal autotransplant and remain pain free. These cases support the UW-LPHS-test as a diagnostic maneuver to determine which patients may benefit from renal autotransplant.